ONOMATOPOEIA PHENOMENON IN ENGLISH AND UZBEK FICTION (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
This study investigates the onomatopoeia phenomenon in English and Uzbek fiction. The study further explores the phonetic, semantic, and stylistic characteristics of onomatopoeic expressions in both languages. While English onomatopoeic forms tend to be concise and structurally simple, Uzbek forms often display morphological complexity and expressive variation. Despite these differences, both languages employ onomatopoeia as an effective stylistic device to engage readers, evoke sensory experiences, and reinforce the aesthetic value of fictional texts. The findings of this comparative analysis demonstrate that onomatopoeia serves not only as a means of sound imitation but also as a powerful artistic tool shaped by linguistic structure and cultural context. Understanding the similarities and differences in the use of onomatopoeia in English and Uzbek fiction contributes to broader studies in stylistics, comparative linguistics, and literary translation.